Probiotics and oral health : myth or reality? - Shetty, Mamatha S.; Shetty, Yashaswini S. (Journal of Health and Allied Sciences NU, 2015)
Human being ingests a large number of living microorganisms, predominantly bacteria. Although these organisms are naturally present in food and water, they can also be deliberately added during the processing of foods(1). For several decades now, bacteria called Probiotics have been added to some foods because of their beneficial effects on human health. Several clinical studies have already demonstrated the effectiveness of certain probiotics in the treatment of systemic and infectious disease such as diarrhea, crohns disease, cardiovascular diseases, oropharyngeal infections and cancers(2)Potential application of probiotics for oral health has recently attracted attention of several teams of researchers. The concept of probiotics therapy has been considered for application in oral health. Dental caries, periodontal diseases and halitosis are among the oral disorders that have been targeted. Hence, this section gives a brief idea of probiotics and its application in oral health.
Keywords: Probiotics; oral health; oral diseases